(untitled) (Fiep Bulletin - online, 2019)
Orienteering is an individual sport that aims to travel a certain distance on varied and unknown terrain, with the aid of amap and a compass. The objective of this study was to verify if the practice of Sports Orienteering improves the quality of life andthe cognitive, physical and social performance of university students who joined this sport to their routine of physical activities.For that, the WHOQOL-BREF questionnaire was applied to 13 university students to evaluate their quality of life, and aquestionnaire with specific questions related to the experience of the sport and its influence on daily life. The results show that inthe physical domain, the general mean of the participants was 3.8, in the psychological domain the mean was 3.7, in the socialrelations domain the mean was 3.6 and in the environmental domain obtained mean of 3.2. Regarding the perception of thequality of life of the students, the mean was 4 and, with regard to their satisfaction with health, an mean of 4.1 was found. Theresults show that students who practice sports have a quality of life considered regular and their perception and satisfaction withtheir good health. Regarding the cognitive, physical and social performance, based on the answers of the applied questionnaire,the evaluated ones indicated that after their insertion in the sport all these aspects were better developed, indicating that the sportcontributed to the improvement of the subjective perception of the students in these fields evaluated.